Ionic conductivity and dipolar effects of glucose enzymatic solution and fruit juices determined using developed dual frequency microwave glucose biosensor - Jafari, Fariba (2012)
A dual frequency microwave glucose biosensor is developed based on microwave attenuation and is used for measuring the concentration of glucose content of fruit juices. In this biosensor system two source frequencies 1GHz and 16.5GHz along with the electronic switch were used to send the signal through the power divider to the couple of microstrip sensors. Two wideband detectors were used to measure the amplitude of the reflected signal from the sensor. The whole system was interfaced to the labtop PC through the National Instruments data acquisition card, with the help of software written in Labview graphical panel. It guides the user to perform measurements easier and faster. This biosensor is suitable for a broad range of glucose content ranging from 0.01M to 3M (Molar) which can help to control the quality of the juice in food industry. It is based on the variation of the dielectric properties of the glucose solution after reacting with the enzyme (GOx). Therefore the glucose content of solution sample can be finding by measuring the attenuation of the signal through the sample. The microstrip sensor was fabricated using RT-Duriod with dielectric properties of 2.2-j0.002 as the substrate, with operating frequency at 16.5 GHz. Using this type of coaxial sensor only the small part of sample is needed to contact with the microstrip line, therefore the measurement can be done with lower cost, more accuracy and in a shorter time. Theoretical analysis based on quasi-transverse electromagnetic mode (TEM mode) in four layered microstrip is carried out to evaluate design parameters such as microstrip characteristic impedance, effective dielectric constant, length and thickness due to the sensitivity of the sensor. The analysis of the complex electromagnetic waves in this system is presented using signal flow graphs and solved by Mason's non-touching loops rules. To this end Visual Fortran programs is written and documented to evaluate all the design parameters needed and to estimate the microstrip patterns. In the other part of this study, investigation was made to find the optimum ratio of enzyme reaction with glucose solution and highest sensitivity of this technique, with the studying of the dielectric properties of the glucose samples. The ionic conductivity and dipolar effect on the polarization of the glucose solution after reacting with enzyme has been studied using two frequencies; one was below 2GHz and one above that amount at room temperature. In the purpose of verifying this sensing technique the results of the glucose solution samples has been compared with the results for some type of fresh fruit juice samples. It was found that the dielectric loss of the samples is affected by frequency, concentration of glucose and ratio of enzyme reaction. The results of the different for dielectric loss of the solution (glucose+ enzyme) and glucose, shows the changes are preferable for derivation of glucose concentration. The dual frequency biosensor was used to measure the attenuation and analysis of the results at 1GHz and 16.5 GHz has been done completely. This biosensor tested on four types of fruit juices in the range of 0.5M to 3.1M glucose concentration. The biosensor has predicted glucose concentration with the accuracy of concentration detection ±0.14 M using average method and can goes even up to ±0.13 M using weighted average method. For the stability of this glucose biosensor, studying the effect of operating time on the stability of this biosensor and enzyme behavior within 45 minutes of operating glucose at room temperature (25°C). This microwave glucose biosensor has the limit of detection of glucose concentration in solution in quiet higher than vivo measurement or medical application; therefore it can be used more in food industry. Therefore the study of the development of the dual frequency system using microwave technique will give benefit to the future application of this technique application in food industries especially for products such as juices, milk and etc, where both ionic conductivity and dipole effects are considering simultaneously.